2020
DOI: 10.1186/s40623-020-01159-5
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of a moderate earthquake, eastern flank of the Red Sea, Saudi Arabia

Abstract: The present study presents the analysis of a moderate earthquake (Mw 4.0) and its largest aftershocks located along the Red Sea coast, southwestern Saudi Arabia, with the aim to understand the enigma of peculiar seismicity in the Arabian Shield. We analyzed a high-quality waveform dataset collected from ten well-recorded earthquakes of moment magnitude ranging from 2.0 to 4.0 in order to determine the hypocenter locations and focal mechanisms. The focal mechanisms were retrieved from the regional moment-tensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(61 reference statements)
1
3
0
Order By: Relevance
“…It is worth-knowing that the conjugate fault system, evidenced by the gravity data analysis and inherited in the region, plays a vital role in Arabian Shield. This finding is consistent with the results obtained from recent studies of Abdelfattah et al (2017bAbdelfattah et al ( , 2020 for earthquake sequences in the Jizan and Namas seismogenic zones, located in the Arabian Shied southward of the HL seismogenic zone.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is worth-knowing that the conjugate fault system, evidenced by the gravity data analysis and inherited in the region, plays a vital role in Arabian Shield. This finding is consistent with the results obtained from recent studies of Abdelfattah et al (2017bAbdelfattah et al ( , 2020 for earthquake sequences in the Jizan and Namas seismogenic zones, located in the Arabian Shied southward of the HL seismogenic zone.…”
Section: Discussionsupporting
confidence: 93%
“…The current geodynamic process acting in the Red Sea is characterized by the extensional tectonic stress regime as accommodated by the Arabian plate's divergence movement away from the African plate (Stoeser and Camp 1985;Abdelfattah et al 2020). Within the Red Sea's eastern flank, the stress regime is presumably imported by a shallow active asthenosphere (Abdelfattah et al 2017b); forming a complex structure consisting of several fault styles differently orientated, such as the NW-SE dykes and the NNW normal faults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have suggested that a low friction coefficient in a weak zone along the fault may be causative for seismic activity (Pınar et al, 2010;Fojtíková and Vavryčuk, 2018;Abdelfattah et al, 2020). Furthermore, a low friction coefficient indicates low stress drops in the source, as high shear stress may not be accumulated in extensional tectonics (Abdelfattah et al, 2020).…”
Section: Resultsmentioning
confidence: 99%